2016
DOI: 10.1177/0890334416637801
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pasteurized Donor Human Milk during Refrigeration

Abstract: Dear Editor, We have attentively read the Vickers et al 1 article about storage of pasteurized donor human milk (PDHM) at 4ºC for 96 hours. In this study, its authors resolve that there was no evidence of microbes in PDHM that had been defrosted and stored at 4ºC for up to 9 days. Previously, Slutzah et al 2 had shown how bacterial growth in fresh milk remained unchanged for 96 hours and, therefore, concluded that fresh mother's milk may be stored at refrigerator temperature for as long as 96 hours. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Initially, 19 studies that included HPDHM were identified. Three (16%) did not describe the length of storage time, [20][21][22] one (5%) did not report outcomes specifically for HPDHM, 23 and one (5%) was not peer reviewed, 24 leaving a final total of 14 studies included in this review (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, 19 studies that included HPDHM were identified. Three (16%) did not describe the length of storage time, [20][21][22] one (5%) did not report outcomes specifically for HPDHM, 23 and one (5%) was not peer reviewed, 24 leaving a final total of 14 studies included in this review (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…As part of a larger study on unpasteurized milk (35 samples of unpasteurized milk), Slutzah et al (2010) analyzed 5 samples of pasteurized milk that were kept refrigerated for 96 h; they observed that neither the pH nor the concentration of fatty acids changed, and there was no bacterial growth. In a previous study conducted in our unit (Tobío-Gimeno et al, 2016), we analyzed the pH of 30 samples of unfrozen pasteurized donor milk kept in a refrigerator, and the pH remained unchanged for 4 d. A more recently published study analyzed bacterial growth in refrigerated pasteurized milk and found no bacterial growth in 7 d (Meng et al, 2016).…”
mentioning
confidence: 99%